LINGUISTIC SOLIDARITY IN PRO-PALESTINIAN ARAB DIGITAL ACTIVISM: A CYBERPRAGMATIC ANALYSIS - Rohmah, Alfia; Farisah, Lulukatul (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Amid growing global attention to the Palestinian cause, Arabic-language social media has become a key site for expressing solidarity and identity. This study addresses the importance of examining how digital discourse constructs humanitarian solidarity through linguistic and multimodal practices. Drawing on Peled’s concept of linguistic solidarity and Yus’s framework of cyberpragmatics, the research adopts a qualitative approach to analyze posts, hashtags, emojis, and visuals on X (Twitter) that convey support for Palestine. The findings indicate that digital solidarity emerges through the pragmatic interaction of linguistic, visual, and affective resources. Arabic serves as a marker of collective identity and cultural belonging, while English and digital symbols facilitate transnational reach and inclusivity. This interplay underscores how online language functions as a performative act that not only communicates political stance but also enacts empathy and shared humanity. Ultimately, the study contributes to understanding the moral and pragmatic dimensions of language in digital activism and highlights its role in sustaining transnational networks of solidarity.